Effects of Hirudin on Activated Partial Thromboplastin Time Determined with Ten Different Reagents - Tripodi, Armando; Chantarangkul, Veena; Arbini, Arnaldo A; Moia, Marco; Mannucci, Pier Mannuccio (Thrombosis and Haemostasis, 1993)
Hirudin prolongs the APTT when added to normal plasma and the extent of prolongation depends on the type of reagent used. The aim of this study was to compare the dose-response curves of 10 widely used APTT reagents for linearity and parallelism. On each of 10 working days a normal pooled plasma was mixed with increasing amounts of recombinant hirudin (HBW023) ranging from 0 to 5 μg/ml and tested for APTT by photo optical coagulometer. Within each working day, clotting times were measured in duplicate and the order of testing with each reagent was changed every day. Results were expressed as ratios of clotting times with hirudin to clotting times without hirudin, and the values plotted against the hirudin concentration on a log-log scale. The dose-response curves for all reagents were linear over 0.3–1.2 μg/ml. The reagent-related slopes ranged from 0.225 ± 0.003 to 0.303 ± 0.003 (mean ± SE) and were significantly different. Precision studies indicated that the least sensitive reagent was also the least precise. These findings indicate that the clotting time values obtained for patients treated with hirudin will vary depending on the APTT reagent used.